Association of the genetic polymorphisms of the ACE gene and the eNOS gene with lupus nephropathy in northern Chinese population - Lian H; Lu F; Zhao Y; Li Y; Jin Z; Guo R; An J; Li X; Liu P; Zhao Y; Jin X (BMC, 2010)
Abstract Background It has been reported that some single nucleotide polymorphisms (SNPs) of the angiotensin converting enzyme (ACE) gene and the endothelial nitric oxide synthase (eNOS) gene are associated with the development of systemic lupus erythematosus (SLE) and the progression of nephropathy. The aim of this study was to evaluate the possible association between six SNPs (A-5466C, T-3892C, A-240T, C1237T, G2215A and A2350G) of the ACE gene and two SNPs (T-786C and G894T) of the eNOS gene with lupus nephropathy in a northern Chinese population. Methods In this study, 225 patients with lupus nephropathy were compared to 232 healthy controls, matched by gender, age and ethnicity. Following the extraction of genomic DNA from the leukocytes in the peripheral blood, the genotypes of the eight selected SNPs were determined by the method of PCR-RFLP; the haplotypes were inferred using PHASE 2.1. The associations between the SNPs and the risk of lupus nephropathy were analyzed using Chi-square test and Logistic regression with SPSS13.0 software. Results Statistically significant differences of the allele frequency distribution of three SNPs (A-5466C, A2350G and G894T) were observed between cases and controls (P < 0.05). Among the 53 haplotypes identified, the frequencies of five haplotypes (CTTCGA, ACTTAA, ACATGG, ACACGG and ATTCGA) were significantly different between cases and controls (P < 0.05). Conclusions Our study indicated an association between the risk of lupus nephropathy and the sequence variations of both the ACE gene and the eNOS gene, which may play an important role in the pathogenesis of lupus nephropathy in the northern Chinese population. Further studies are warranted to validate our findings.